INCREASING THE EFFICIENCY OF THE USE OF TRUCKS IN THE REGIONS OF THE REPUBLIC OF UZBEKISTAN: STRUCTURE AND FEATURES - Aytieva Sevara Allaberdievna (Scholar Express Journals, 2022)
This article discusses the structure of the Uzbek freight transportation market, analyzes its main participants: carriers, forwarders, logistics operators, pays attention to the main trends, problems and features of the development of transport and forwarding activities.
Keywords: structure and features; increase; trucks; efficiency